Multidisciplinary management of Complex Regional Pain Syndrom Type 1 in children admitted to Red Cross War Memorial Hospital: A case series describing long-term effects on pain, function and quality of life - Nock, Mariasa (Department of Anaesthesia, 2018)
Background: Complex regional pain syndrome (CRPS) is characterised by neuropathic-type pain in a regional distribution with associated signs and symptoms including: swelling, change in temperature, change in skin colour and motor dysfunction. Although CRPS is not a common condition, the disease burden is high and can lead to long-term impairment and disability. Current guidelines for the management of paediatric CRPS are mostly extrapolated from adult data. Literature regarding treatment and long-term prognosis of paediatric CRPS is sparse and often lacks well-defined and reproducible outcome measures. Aim: This study aims to assess the efficacy of treatment of CRPS Type 1 in children admitted to Red Cross War Memorial Children's Hospital (RCWMCH) in eliminating pain and improving function. Methods A retrospective folder review and follow-up telephonic survey of all children admitted to RCWMCH over a 5 year period was performed. Long-term follow-up was defined as a minimum of 6 months after discharge from hospital. Follow-up questionnaires included the Faces Pain Scale, and the Paediatric Quality of Life Inventory Version 4 generic core scales (PedsQL 4.0) Results: Nine children with confirmed CRPS Type1 were included in the study, all of whom participated in long-term follow-up. Children received in-hospital treatment from a multidisciplinary team, including intensive physiotherapy and psychological therapy. Pharmacological treatment consisted of an intravenous ketamine infusion and varying combinations of gabapentin, clonidine and amytriptilline. One child received epidural local anaesthetic infusion. On average, pain scores improved by 67.8% by the time of discharge. At an average long-term follow-up interval of 10.3 months (ranging between 6 to 21 months), the pain score had worsened by 10.5% compared to discharge. Two children (22.2%) experienced complete recovery while the remainder experienced partial recovery. Three children (33.3%) suffered a relapse, of which one recovered completely. At long-term follow-up, children for whom PedsQL 4.0 data was available from admission all demonstrated clinically meaningful improvements in all four functional domains (physical, social, emotional and school). Children scored on average similar to healthy peers in terms of social, emotional and school function, but worse in terms of overall quality of life. The area most affected was that of physical function, in which children with CRPS scored worse than other children with chronic health conditions. Conclusion: Children with CRPS experience significant improvement in pain and function with an in-patient, multidisciplinary, non-invasive treatment approach. Most children return to a level of school functioning comparable to healthy peers. However, the rate of complete recovery is low, relapse is common, and most children have significant persistent impairment of physical function. We recommend a long-term support program for children with CRPS and their families, and standardisation of follow-up intervals and outcome measures to enable comparison between future studies.